MENINGKATKAN KEMAMPUAN MENGENAL SIFAT CAHAYA MELALUI METODE DEMONSTRASI BAGI ANAK TUNA RUNGU DI SLB NEGERI AMPEK ANGKEK - Ema Novera (Jurnal Penelitian Pendidikan Khusus, 2012)
The research of beginning the set of problems find that from SLB in Ampek Angkek, the deaf student in DV/B grade do not knot about about radiance and characteristics. The teacher do not use the effective of methods in learning, they must use of alternative in solve of problems, the first fault they use of demonstration methods. Kinds of the research can use for classroom action research in collaboration with classmate and teacher. The subject of research is two the deaf student in DV/B grade. The result of research can be use one one cycle with demonstration methods. In cycle AS can be understand about of meaning radiance, sourch of it. It can be dispersed trough of transparent things, spreading straight line. It can refraction and analyzing for get the good research . we must do to adding the time in the meeting. The summarize of demonstration method can be increasing the ability to know about the radiance of characteristic for deaf student and as suggestions to teacher. For applying , the method can be continuing of the same subject matters.